Translating Sexist Expression Toward Men: Analysis of Translation Technique and Its Impact on Meaning Equivalence in Naomi Alderman's the Power - Siswanti, Sandra Damar; Rahmawati, Anisa Dien; Permatasari, Sherli Putri (Makassar State University, 2025)
Abstract. The aim of this research is to explore the shift in sexist language directed at men in an English novel that has been translated into Indonesian. The research aims to identify sexist expressions in the original English novel, analyze the translation techniques used in the Indonesian version, and evaluate their impact on the textual equivalence of the translated text. The theory used in this research is Benatar (2012) second sexism, Wareing (2004) classification of sexist expressions and Molina and Albir’s (2002) framework on translation techniques. The result shows that based on Wareing's four categories of sexist expressions, there are three types of sexist expressions present in the novel. The most frequently used is sexism in discourse, contributing 67% of all sexist expressions. The second most common type is insult, making up 22%, and the last is symmetry and asymmetry, at 11%. The second finding indicates that the most frequently used translation technique for rendering sexist expressions toward men in the novel is literal translation followed by modulation. The third finding shows that literal translation preserves structural cohesion by maintaining the sentence structure of the source text, while modulation and established equivalence enhance cultural cohesion by adapting phrases that may not directly translate but retain the original meaning. Therefore, to translate sexist expressions, it is crucial to select appropriate translation techniques that balance fidelity to the source text with cultural relevance in the target language.Keywords: sexists’ expression, second sexism, translation technique, textual equivalence